Effects of stair task training on walking ability in stroke patients - Choi, Yong-Kyu (J Phys Ther Sci, 2017)
[Purpose] The aim of this study was to determine the effect of stair task training on gait abilities by conducting stair task training. In this training, step training is applied in various directions with hemiplegia patients. [Subjects and Methods] Thirty-six patients with stroke were selected on the basis of inclusion and exclusion criteria, and they were randomly divided into eighteen patients in the experimental group and eighteen patients in the control group via draw. [Results] In this study, the Dartfish program was used to measure gait capabilities. Experiment group showed a statistically significant improvement in the swing phase time of the affected lower extremity compared to control group. [Conclusion] It was found that the stair task training group had effective results in the swing phase time of the affected lower extremity compared with the group that applied weight support on the affected lower extremity and balance training.